Nilai-Nilai Pendidikan dari QS. An-Nisa Ayat 36 tentang Bentuk-bentuk Akhlakul Karimah - Lutfi Sabila; Nuroni, Enoh; Surbiantoro, Eko (UNISBA Press, 2024)
Abstract. Fornication is a human trait that prompts itself to distinguish between good and bad works, so it is called akhlakul karimah or praiseworthy. The results of this study reveal in qs.s. an-nisa verse 36 that no man's morals belong to god. Chastity to parents, neighbor's morals and community, chastity to the close of kin, to family, morality to the fatherless and the poor. The results of this study reveal in qs.s. an-nisa verse 36 that no man's morals belong to god. Chastity to parents, neighbor's morals and community, chastity to the close of kin, to family, morality to the fatherless and the poor. The value of education embodied in qs -nisa verse 36 is (1) the value of the worship of education in which the subjection to act through all the commands of god is lifted. (2) the value of tauhid education means essaying god n. (3) the value of chastity education is the first priority of the sending of the prophet (peace and blessings be upon him). , in addition to perfecting the divine teaching. Abstrak. Akhlak merupakan perangai manusia yang mendorong dirinya untuk membedakan perbuatan yang baik maupun yang buruk, maka hal ini disebut akhlakul karimah atau akhlak yang terpuji. Akhlak ini dinilai menjadi materi yang sangat penting dalam membentuk pribadi yang baik. Karena akhlak merupakan salah satu yang sangat penting dalam kehidupan sehari-hari dan penting juga dalam ajaran islam. Hasil penelitian ini mengungkapkan di dala Q.S An-Nisa ayat 36 bahwa akhlakul karimah seseorang mencakup akhlak kepada Allah Swt. Akhlak kepada orang tua, akhlak tetangga dan Masyarakat, akhlak kepada karib kerabat, kepada keluarga, akhlak kepada anak yatim dan orang miskin. Nilai-nilai Pendidikan yang terkandung dalam Q.S An-Nisa ayat 36 adalah:(1) nilai Pendidikan ibadah dimana ketundukan untuk melaksanaan segala perintah Allah Swt. (2) Nilai Pendidikan tauhid yang berarti meng-Esa-kan Allah Swt. (3) Nilai pendidikan akhlak merupakan prioritas utama diutusnya Nabi Muhammad saw., di samping menyempurnakan ajaran Allah Swt.